The Role of Exchange Rate in Moderating Effect of Sharia Shares, Sharia Mutual Funds, and Foreign Debt on National Economic Growth Rate in 2011-2023 - Mukarromah, Indriya Zayinul; Bawono, Anton (El-Qist: Journal of Islamic Economics and Business (JIEB), 2024)
This study aims to investigate the moderating role of exchange rates in the relationship between Islamic stocks, Islamic mutual funds, and foreign debt on national economic growth in Indonesia from 2011 to 2023. Utilizing a quantitative approach with Moderated Regression Analysis (MRA), this research employs quarterly time-series data sourced from Indonesia’s Financial Services Authority, Bank Indonesia, and the Central Bureau of Statistics. The findings reveal that the exchange rate has a positive and significant impact on economic growth, while foreign debt exerts a positive yet insignificant effect. Furthermore, the exchange rate significantly moderates the impact of foreign debt on economic growth but fails to moderate the influence of Islamic stocks. Notably, Islamic mutual funds and Islamic stocks were excluded from the final model due to multicollinearity. This research contributes to the international discourse by providing empirical evidence from an emerging Muslim-majority economy, highlighting how currency stability plays a pivotal role in shaping the interaction between external financial instruments and economic growth. The study underscores the importance of exchange rate management in enhancing macroeconomic resilience, particularly within the context of Islamic financial markets in developing countries.